Analisis Strategi Pengembangan Kwirausahaan Mahasiswa Ekonomi di Era Globalisasi - Gita Kurniasari Sembiring; Zuhrinal M.Nawawi (Economic Reviews Journal, 2022)
The purpose of this research or writing is to analyze the entrepreneurship development strategy of economic students in the current era of globalization on the growth and development of the Indonesian economy and development. Entrepreneurship aims to increase competitiveness, provide employment, reduce unemployment and poverty. The development of entrepreneurship continues to increase which until now in Indonesia there are 52.6 million micro, small and medium enterprises (Bisnis.Com, 7 March 2013). The development of entrepreneurship that continues to increase must be balanced with aspects and strategies as well as the role of the government that can optimize entrepreneurial potential. The success of MSME development (entrepreneurship) from the qualitative aspect according to Nasution is reflected among others from the increased understanding of entrepreneurship and the increase in entrepreneurship and product quality which have a direct impact on increasing entrepreneurial competitiveness. Globalization and liberalization are a reality, today's entrepreneurs can no longer avoid the situation and conditions of world free trade, especially if they want to play a bigger role in the world economy. To face these challenges, it takes entrepreneurs who are resilient, have global competitiveness and hold noble values ​​and love for their country. Mudradjad Kuncoro in Bisnis Indonesia Daily on October 21, 2008 stated that entrepreneurship is proven to be resistant to crisis and able to survive because 1) it does not have foreign debt, 2) does not have a lot of debt to banks because it is considered unbankable, 3) uses local inputs, 4) is export-oriented. . To grow, develop and face challenges, it is necessary to have policies and strategies from the government that pay attention to entrepreneurs in increasing the competitiveness and quality of entrepreneurship in the face of the global financial crisis. Keywords: entrepreneurship development strategy, economic students, globalization.